The Impact of Programmed Death-Ligand 1 Expression on the Prognosis of Early Stage Resected Non-Small Cell Lung Cancer: A Meta-Analysis of Literatures - Shi, Tao; Zhu, Shuai; Guo, Hengjuan; Li, Xiongfei; Zhao, Shikang; Wang, Yanye; Lei, Xi; Huang, Dingzhi; Peng, Ling; Li, Ziming; Xu, Song (Frontiers in Oncology, 2021)
Introduction: Previous studies have demonstrated that programmed cell death-ligand 1 (PD-L1) serves as biomarker for poor prognosis and survival in advanced-stage non-small-cell lung cancer (NSCLC) patients. However, the merit of PD-L1 expression to predict the prognosis of early-stage NSCLC patients who underwent complete resection remains controversial. In the present study, we performed a meta-analysis to investigate the relationship between PD-L1 expression and prognosis in patients with early-stage resected NSCLC. Methods: Electronic databases, including PubMed, EMBASE, and the Cochrane Library, were searched until July 23 2020, for studies evaluating the expression of PD-L1 and the prognosis of resected NSCLCs. Hazard ratios (HRs) with 95% confidence intervals (CI) of overall survival (OS) and disease-free survival (DFS) were pooled and analysed. Heterogeneity and publication bias analyses were also assessed. Results: A total of 15 studies involving 3790 patients were considered in the present meta-analysis. The pooled HR indicated that PD-L1 expression related to a much shorter DFS (HR =1.56, 95% CI: 1.18-2.05, p<0.01), as well a significantly worse OS (HR =1.68, 95% CI: 1.29-2.18, p<0.01). Furthermore, our analysis indicated that PD-L1 expression was signiﬁcantly associated with gender (male vs. female: OR=1.27, 95% CI:1.01-1.59, p=0.038), histology (ADC vs. SCC: OR=0.54, 95% CI:0.38-0.77, p=0.001), TNM stage (I vs. II-III: OR= 0.45, 95% CI:0.34-0.60, p=0.000), smoking status (Yes vs No: OR=1.43, 95% CI:1.14-1.80, p=0.002) and lymph node metastasis (N+ vs N-: OR=1.97, 95% CI:1.26-3.08, p=0.003). Conclusions: The results of this meta-analysis suggest that PD-L1 expression predicts an unfavourable prognosis in early-stage resected NSCLCs. The role of personalized anti-PD-L1/PD-1 immunotherapy in the adjuvant settings of resected NSCLC warrants further investigation.